Pergeseran Militer Politik ke Militer Profesional; Studi Tentang Keberadaan Komando Teritorial Era Reformasi - Nugraha, Ary (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The existence of the Territorial Army Command Institute for New Order have negative impact in the lives of democratization . Since the passing of the post- 1998 reforms in order to impact the immediate reform of the TNI . territorial development and function Koter Army Institute started getting noticed by the public . Pros and cons also extends both external and internal military . Pro - reform elements of society , pro-democracy and pro- military professionals , both individuals and institutions , such as Agus Widjojo , Wirahadikusumah , Awaloedin Djamin , Impartial , and Propatria Pusdeham openly communicated its refusal . Broadly speaking, the function of territorial and territorial army units they value against the idea of a professional army . Functions according to their territorial besides not directly related to military functions , also not in accordance with the needs of national defense and development strategy of modern warfare . They rejected the Army Institute Koter and territorial development function as assessed ignoring the threat of modern military state and the dynamic nature of the enemy that complicate the development of national defense posture - related military force ( military strength) , the ability of the military ( military capability) and the deployment of military forces (military deployment ) . the extent of the territorial command functions in the reform era has led to a professional military . What is the urgency of the territorial command of the army in the era of reform and how the views of civil respond. Then Permanent retention Koter Army Institute in the Reform Era becomes. interesting study to be discussed.Key : shift , the existence , territorial commands , reform